Pendidikan Kesehatan tentang Deteksi Dini Kanker Payudara melalui Pemeriksaan Payudara Sendiri (SADARI) - Julaecha Julaecha (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
Breast cancer is one of the leading causes of death and many types of cancer occur in women. The incidence of breast cancer increases with age, however, young age is not a safe guarantee of breast cancer. The high incidence of breast cancer resulted in not a few sufferers of breast cancer that led to death. Signs and symptoms of breast cancer can be found as early as possible, the higher the cure rate. Breast self-examination (BSE) is one effective step if done as early as possible when women reach reproductive age. The purpose of community service is that teenagers consciously want to do breast self-examination routinely every month so as to reduce and reduce the risk of breast cancer. The method used by giving counseling and demonstration about BSE techniques to young women. An indicator of the success of this activity is that young women are able and able to conduct self-examination. Community service is carried out in Sungai Putri, Danau Sipin Sub-district, Jambi City on December 2018 - January 2019. The results of this activity are all young women understand and understand and can do their own breast examination (BSE).